Functional genomics towards personalized healthcare and systems medicine. (May 2011) - Siest, Géérard; Nezhad, Mohsen Azimi; Bagrel, Denyse; Shamieh, Said El; Lambert, Daniel; Ndiaye, Ndeye Coumba; Shahabi, Payman; Visvikis-Siest, Sophie
The 5th Biologie Prospective Santorini Conference explored the themes of systems biology, nutrigenomics and pharmacogenomics, all of which are related to personalized health, personalized therapy and personalized medicine. The conference started with a satellite meeting on genome-wide scan studies where the need for simplified models, the quality of the phenotypes and the input of epigenetics were dominant remarks. All of the omics approaches were then applied during the 3 days'' sessions to multifactorial diseases (e.g., diabetes, atherosclerosis, cancer and inflammation) and often focused on gene––gene and gene––environment interactions. Afterwards, a fundamental session on drug metabolism, theranostics and pharmacogenetics and their practical aspects showed that the translation to clinical practice is finally happening although much slower than expected.